Development status and future prospect of non-aqueous potassium ion batteries for large scale energy storage. (June 2019) - Zhang, Jundong; Liu, Tingting; Cheng, Xing; Xia, Maoting; Zheng, Runtian; Peng, Na; Yu, Haoxiang; Shui, Miao; Shu, Jie
Abstract: Lithium ion batteries (LIBs) as the mainstream rechargeable batteries are widely used in industrial production and life. However, it is hard to meet the demand in the future due to the lack of lithium resources. At the same time, increasingly scarce lithium resources will increase the cost of LIBs. In contrast, potassium is abundant in the earth's crust, and available researches suggest that rechargeable potassium ion batteries (KIBs) may be a promising substitute for LIBs. In this paper, the research progress of non-aqueous KIBs is reviewed, including cathode materials, anode materials, electrolytes, binders, opportunities and future challenges. Firstly, cathode and anode materials are summarized according to the different reaction types. Secondly, the application and influence of electrolytes and binders for non-aqueous KIBs are also discussed. Moreover, in order to promote the advancement for non-aqueous KIBs, the main future challenges and some solutions are also proposed. Graphical abstract: Image 1 Highlights: The present situation and advantages of non-aqueous KIBs are discussed. A review of electrode materials, electrolytes and binders for KIBs. Challenges and opportunities for KIBs in the future are pointed out.